2018
DOI: 10.21037/tlcr.2018.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic trial of a multidisciplinary lung cancer care model in a community healthcare setting: study design, implementation evaluation, and baseline clinical results

Abstract: This study demonstrates a comprehensive implementation of a multidisciplinary model of lung cancer care, which will advance the science behind implementing this much-advocated clinical care model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…MDTs, involving close coordination from a range of specialists, including physicians, surgeons, oncologists, pathologists, radiologists, nurses, and allied health care personnel, have become standard of care in lung cancer treatment in many centers around the world. MDT data can provide important information on lung cancer outcomes and on the impact of MDT care, which is associated with a range of clinical benefits as noted above, as well as valuable insights into current practices . Data linkage to other sources can enhance this further .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MDTs, involving close coordination from a range of specialists, including physicians, surgeons, oncologists, pathologists, radiologists, nurses, and allied health care personnel, have become standard of care in lung cancer treatment in many centers around the world. MDT data can provide important information on lung cancer outcomes and on the impact of MDT care, which is associated with a range of clinical benefits as noted above, as well as valuable insights into current practices . Data linkage to other sources can enhance this further .…”
Section: Discussionmentioning
confidence: 98%
“…Multidisciplinary team (MDT) care in lung cancer confers a number of clinical benefits associated with MDT care, including improvement in survival, treatment receipt, modification of treatment plans compared with premeeting plans, accuracy of staging, adherence to international treatment recommendations, and patient‐related outcomes . However, detailed evaluation of the data collected during meetings, which may overlap with but also differ from comprehensive registry data, and how the data are used by MDTs is sparsely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-centered outcomes, which are as important, if not more so in patients with cancer, are also largely unstudied in thoracic oncology. One preliminary qualitative study has shown high satisfaction with clinic co-location of services for lung cancer patients (11).…”
Section: Measuring Qualitymentioning
confidence: 99%
“…A multidisciplinary team (MDT) consists of specialists with different backgrounds, skills and clinical experience, working together to recommend the best clinical pathway both in the case of planned treatments or to establish the most appropriate follow-up program [ 2 ]. MDT meetings in oncology can also be defined as tumor boards (TB); they offer several clinical benefits for global care: overall survival improvement [ 3 , 4 ], receipt of therapy [ 5 , 6 ], optimizing of treatment plan compared with pre-MDT hypotheses [ 7 , 8 ], staging accuracy [ 9 ] and global adherence to guidelines and international evidence-based recommendations [ 10 , 11 , 12 , 13 ].The MDT meeting can be considered as a common platform to coordinate the delivery of care by merging different clinical expertise in a single setting and can therefore be defined as a regularly scheduled discussion of clinical cases with the participation of physicians from different specialties such as surgeons, oncologists, radiotherapists, pulmonologists, pathologists, anesthesiologists, nurse specialists and other specialists when needed [ 14 ]. MDT meetings are suggested by many lung cancer treatment guidelines [ 15 , 16 , 17 ] but their organization and management is quite heterogeneous, varying across countries, hospitals and departments.…”
Section: Introductionmentioning
confidence: 99%